Medicinal Earthworm: Speciation and Bioaccessibility of Arsenic and Its Potential Health Risks - Li, Yaolei; Li, Hailiang; Zan, Ke; Wang, Ying; Zuo, Tiantian; Jin, Hongyu; Zhang, Bing; Ma, Shuangcheng (Frontiers in Pharmacology, 2022)
Arsenic in environmental health has caused public concerns all over the world. However, high levels of arsenic residues in medicinal animals have not received enough attention. Medicinal earthworms are consumed widely in China, but its arsenic potential health risks to humans are unknown. This work investigated the total concentration, bioaccessibility, and speciation of arsenic in earthworms by ICP-MS and HPLC-ICP-MS to evaluate its potential health risks to humans. Arsenic was found in all earthworms at concentrations ranging from 0.4 to 53.6 mg kg−1. The bioaccessibility of arsenic (bAs) varied significantly and ranged from 12.1 to 69.1%, with inorganic arsenic (iAs, including As(III) and As(V)) as the predominant species. Furthermore, a small amount of arsenobetaine (AB) was found. The estimated daily intake dose (EDI), hazard quotient (HQ), and carcinogenic risk (CR) of arsenic in most of the samples exceeded the safe threshold level. Results from this study indicated that the potential health risks by the consumption of earthworms may not be negligible. Herein, recommendations for the use of earthworms and regulatory recommendations for arsenic limit standards were proposed. This study reminds us that more control and monitoring of arsenic in medicinal animals should be carried out.